Active labour market policy in East Germany: waiting for the economy to take off - Michael Lechner; Conny Wunsch (Institute for the Study of Labor (IZA), 2006)
We investigate the effects of the most important East German active labour market programmes on the labour market outcomes of their participants. The analysis is based on a large and informative individual database coming from administrative data sources. Using matching methods, we find that over a horizon of 2.5 years after programme start the programmes fail to increase the employment chances of their participants in the regular labour market. However, the programmes may have other effects for their participants that may be considered important in the especially difficult situation experienced in the East German labour market.
urn:nbn:de:101:1-20090406359
Keywords: 330; Arbeitsmarktpolitik; Wirkungsanalyse; Beschäftigungseffekt; Neue Bundesländer